Notice of the Ancient Monument, supposed to be that of James, first Earl of Morton, in the Church of Dalkeith - Drummond, James (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author highlights the apse of the old church in Dalkeith, in particular the carved figures found in the apse. Sir Walter Scott argued that these figures represented knights, whereas Drummond believes that James Douglas, fourth lord of Dalkeith and his wife Johan. He then goes on to emphasise the artistry of the monument.